Failures in the regulation of the Colombian state in the management of the public electricity service in Colombia: Electricaribe case 2002-2019 (2021)
For the development of this essay, the electricity service provider company in the Caribbean region of the country Electricaribe SA and the different statutes and positions that the National Government has presented in the face of the privatization of the State public companies will be taken as a case study. The efficient provision of the service. Initially, it was found that the Colombian State has not carried out in the best way the surveillance, control and regulation of the electricity service provider Electricaribe, therefore, the country would have an economic impact for a value that exceeds $ 2.2 billion; of which correspond to the pension and benefit liability with a December 2018 cutoff for a value of $ 1.1 trillion, and $ 1.12 trillion is the value of Electricaribe's debt as of September 2019, these figures vary according to the CPI and the final check is given by CONPES (Portfolio, 2019). According to the PND 2018-2022, the government approved an article in which it would directly or indirectly take charge of this balance left by Electricaribe, for which, by analyzing these decisions, an analysis of the main failures by the authorities will be carried out. Last 3 national governments in the face of the electricity crisis presented by the Electricaribe company.